P19 Use of high fidelity simulation as an effective and acceptable method of training community palliative care specialist nurses: a pilot project. (November 2018) - Walmsley, Rowan; Churm, Deepta
Abstract : Background: In Northumbria we have set up a new team of rapid response community Specialist Palliative Care nurses. New team members with varying experience in this role have been appointed, identifying various educational needs to develop new skills. We undertook this pilot project to establish whether these needs could be met through training using high-fidelity simulation. Simulation training has been described extensively in many settings but, to our knowledge, not in this context. Summary of Work: Three palliative care scenarios (assessment of bowel obstruction, chest infection and a dying patient) were developed using a high-fidelity manikin in a simulation suite replicating a patient's home. These scenarios are ones which arise commonly, and address identified learning outcomes. The scenarios were deliberately chosen to replicate the complexities encountered by nurses as part of their roles, including clinical assessment, examination, decision making and communication. 4 study days were undertaken with 3 nurses on each occasion. Each led on a scenario, whilst the other 2 observed. A debrief followed. The nurses completed evaluation forms on their confidence levels before and after the study day, how realistic the scenarios were, how helpful they found the debrief and whether they would recommend this type of learning experience to their colleagues. They could also provide free text comments. Results: The majority of participants strongly agreed that the cases were a realistic representation of those that they encounter in their usual practice. 10 of the 12 participants felt that their confidence in managing these scenarios had improved following the simulation study day. The remaining 2 participants felt their confidence was the same which they rated as 'good' (4/5 on Likert scale). All participants either strongly agreed or agreed that they felt more confident at managing these scenarios for real. 10 out of 12 participants strongly agreed that the debrief was helpful, and that they would recommend this style of teaching to their colleagues. Free-text comments were generally very supportive of this method of teaching, with little that candidates would like to change about the training days. Conclusions: Simulation training for specialist palliative care nurses is an effective and acceptable method of training. Simulation training is an effective method to simulate community scenarios. Recommendations: Simulation can be used in the training of community specialist palliative care nurses.